1960
DOI: 10.1785/bssa0500020267
|View full text |Cite
|
Sign up to set email alerts
|

The Alaska earthquake of July 10, 1958: Movement on the Fairweather fault and field investigation of southern epicentral region

Abstract: The Fairweather fault is recognizable as a geologic and geomorphic feature from Palma Bay on the southeast at least as far northwest as Nunatak Fiord east of Yakutat Bay, a distance of 200 kilometers along the surface trace. The earthquake of July 10, 1958, was caused by movement on much or all of that segment of the fault: a 10-foot or larger right-lateral offset occurred at Palma Bay where the surface trace trends southeastward under the ocean, and fresh scarps were formed on the south shore of Nunatak Fiord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…References: Hamilton and Myers, in press and written communication, 1966;Miller, 1953;Plafker, George, oral communication. 19&5;Stauder, I960;Tarr and Martin, 1912;Tocher, I960;Tocher and Miller, 1959-The its history suggests that it is an ancestral branch of that system.…”
Section: Lengthmentioning
confidence: 99%
“…References: Hamilton and Myers, in press and written communication, 1966;Miller, 1953;Plafker, George, oral communication. 19&5;Stauder, I960;Tarr and Martin, 1912;Tocher, I960;Tocher and Miller, 1959-The its history suggests that it is an ancestral branch of that system.…”
Section: Lengthmentioning
confidence: 99%
“…Most unequivocal evidence for Holocene displacement, as manifested by seafloor displacements, is on this western trace. In most crossings of the fault trace, where seafloor offsets are well displayed, the sense of movement is northeast side down, showing the same sense of vertical displacement as occurred along the onshore Fairweather fault during the 1958 Lituya Bay earthquake (Tocher, 1960). The more sinuous or eastern trace may be an inactive or relatively less active strand of the fault system; however, several of the profiles also showed some seafloor offset along this trace.…”
Section: Offshore Alaskamentioning
confidence: 73%
“…data, 1965). On the basis of measurements made between 1910and 1960(Hicks and Shofnos, 1965, land in the Petersburg area is rising with respect to sea level at a rate of about 0.4 cm/yr.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…(universal time), 6.6 m of rightlateral movement was measured along with 1 m of ver tical uplift on the southwest side of the fault. Tocher (1960) suggested that, during this earthquake, move ment occurred along much of the Fairweather fault northwestward to Yakutat Bay. George Plafker (oral commun., 1975) reported a segment of the fault located about 58 km north-northeast of Yakutat that is 5 km long with offset drainages indicative of about 1.7 m of right-lateral displacement during the earthquake.…”
Section: Active Faults Close To Yakutatmentioning
confidence: 99%